2018
DOI: 10.3390/cosmetics5030046
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotection of Antioxidant Biocompounds from Grape Pomace: Further Exfoliant Phytoactive Ingredients for Cosmetic Products

Abstract: The goal of this study was to investigate the efficacy and the safety of grape pomace (Vitis labrusca L.) obtained from the winemaking process as an antioxidant raw material for cosmetic formulations. Grape pomace was dried and submitted to extraction with solvents. The extracts were filtered and freeze-dried. The extraction carried out with 75% acetone-water showed a better yield (1.9 g·g−1). High performance liquid chromatography (HPLC) analysis confirmed the presence of ellagic acid as an active biocompound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
(18 reference statements)
2
27
1
1
Order By: Relevance
“…Additionally, fractionation enhanced the active polyphenols present in both crude extracts and intensified the inhibitory activity against collagenase, suggesting the suitability of the extracts for topical cosmetic formulations, which commonly contain between 25 and 100 lmol polyphenols/L (Maidin et al, 2018;Zillich et al, 2015). The potential of GP-derived polyphenols as an antioxidant material in cosmetic formulations was confirmed in another study in which GP extract diminished the cytotoxicity of hydrogen peroxide (H 2 O 2 ) in mouse fibroblasts (Maluf et al, 2018).…”
Section: Skin Healthmentioning
confidence: 84%
“…Additionally, fractionation enhanced the active polyphenols present in both crude extracts and intensified the inhibitory activity against collagenase, suggesting the suitability of the extracts for topical cosmetic formulations, which commonly contain between 25 and 100 lmol polyphenols/L (Maidin et al, 2018;Zillich et al, 2015). The potential of GP-derived polyphenols as an antioxidant material in cosmetic formulations was confirmed in another study in which GP extract diminished the cytotoxicity of hydrogen peroxide (H 2 O 2 ) in mouse fibroblasts (Maluf et al, 2018).…”
Section: Skin Healthmentioning
confidence: 84%
“…Grape pomace is another V. vinifera by-product with important free radical scavenging activities, able to prevent lipid peroxidation [ 152 ]. In this context, a cytoprotective effect of grape pomace in H 2 O 2 induced oxidative stress was investigated by Maluf et al, demonstrating a beneficial impact even at the lowest concentration tested [ 153 ]. These results are in line with the findings of Goutzourelas et al, who demonstrated that, following the exposure to grape pomace extract, the enzymatic activity of gamma-glutamylcysteine synthetase and glutathione S-transferase from endothelial and muscle cells increased [ 129 ].…”
Section: Bioactivity—oral Cavity Conditions As Targets Of Phenolicmentioning
confidence: 99%
“…A theoretical calculation was conducted to investigate the antioxidant activity of the main compounds of apricot pomace extract. The molecules structure of the apricot pomace extract (1)(2)(3)(4)(5)(6)(7)(8) obtained after a geometric optimization procedure is presented in Fig. 4.…”
Section: Theoretical Studies General Quantum-chemical Characteristicmentioning
confidence: 99%
“…In this context, the cheap waste products are particularly interesting for the environmental and economic benefits resulting from their re-use. Agro-industrial by-products are cheap, abundant and sustainable resources which contain compounds with antioxidant, cytotoxic and antimicrobial activities that can be used for synthesis of nanoparticles [4,5], production of food additives [6], as a natural preservative and antioxidant in cosmetic products [7], for inhibition corrosion of metals in corrosive media 1 National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 37, Peremogy Ave., 03056 Kyiv, Ukraine 2 Ukrainian State Chemical-Engineering University, 8, Gagarina Ave., 49066 Dnipro, Ukraine * vorobyovavika1988@gmail.com Ó Vorobyova V., Shakun A., Chygyrynets' O., Skiba M., Zaporozhets J., 2020 [8][9][10][11]14]. Some studies have already been done on byproducts, which could be potential sources of antioxidants [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%